Corona metric spaces: Basic properties, universal lines, and the metric dimension - Rodríguez-Velázquez, Juan Alberto (AIMS mathematics, 2022)
In this article, we introduce the study of corona metric space. After discussing some basic properties of these metric spaces, such as completeness, boundedness, compactness and separability, we provide a necessary and sufficient condition for the existence of universal lines, and we obtain a formula for the metric dimension of corona metric spaces.